Analisis Pemerolehan Bahasa pada Anak Usia 3 Tahun Studi Kasus pada Aisyah Hanum Syahidah - Rania Humairah, Fanisa; Rizkia Alfi, Faiza (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The aim of this research is to find out how the development of language acquisition occurs in children aged 3 years. This research is qualitative-descriptive in which observational research, interviews, and recording methods have been carried out. The subject in this study is Aisyah Hanum Syahidah, who is currently 3 years old. The data obtained in this research is descriptive data. As for the process of data analysis, namely the researcher plays a recording containing the communication process between the researcher and the research subject repeatedly, then examines the vocabulary mentioned by the research subject based on phonological studies. At the age of 3 years, the ability to acquire language in children is quite good, but there are several phonemes that are still difficult to pronounce according to the actual rules. Based on the results of the research, the researchers found three categories of language acquisition abilities in three-year-old Hanum children, namely fluent, moderate and not fluent. At the fluent level, language acquisition by Hanum is [p], [w], [m], [u], [a], [e], [o], [l], [k], [j], [ w] and [y]. At a moderate level, language acquisition by Hanum is [s], [h], [b] and [i]. At the non-fluent level, Hanum language acquisition is [r].